Study of confocal 3D micro X-ray fluorescence analysis technique based on polycapillary X-ray lens. Issue 1 (February 2020) - Meng, Z Y; Xiang, Z J; Liu, Z G; Hao, Y A; Pan, K; Zhou, P; Lin, X Y
Abstract: This study realized the microcell analysis using confocal area formed by a pair of polycapillary X-ray lens, built a 3D micro X-ray fluorescence spectrometer, elaborated the controlling software, and analyzed the 3D scan performance of the set-up via its measured and calculated basic parameters. The depth-detecting performance of the developed set-up was assessed by scanning several samples of Cu-Mo thin film on silicon base and red-green porcelain of Ming dynasty under different conditions. In addition, through surface-adaptive scanning, the scanning and identification of the fractures and fine cracks of the ceramic samples revealed the morphology of samples, which was consistent with the theoretical model.